Enriched I-Q Active Filter Based Harmonics Mitigation in Rectifier-Inverter Fed Induction Motor Drive - Samsher Kadir Sheikh; Manish Jain; Pawan Chandrakant Tapre (Tehnički Glasnik)
In recent decade, an introduction of innovative technological development in power electronics sector is to perform significantly for compensation of power quality issues. The sugar industry's widespread implementation of variable-frequency induction-motor drives cause the electrical distribution systems to become worse. Greater harmonics produced by semiconductor current converters affects the sinusoidal voltage and increase reactive component of current by voltage. To overcome the aforementioned issues, the research paper examines issues of power quality in an induction motor (IM) drive system attached to utility grid system. The addition of filters, which reduces the power quality, issues in induction motor drives by providing lower THD. The IM drive system with an enhanced filter is employed to reduce harmonics produced by power semiconductor switches to keep the three-phase power supply in good condition. So, the instantaneous imaginary controller-based shunt active power filter (I-Q active filter) is employed to lessen the harmonic content that exists in the current at the point of source. To enhance the electrical network system's power quality, the proposed filter is injected parallel within the source and the IM drive system. The outcomes of simulations are analysed and it is executed by MATLAB/Simulink.